2021
DOI: 10.1111/acfi.12789
|View full text |Cite
|
Sign up to set email alerts
|

Corporate carbon accounting: a literature review of carbon accounting research from the Kyoto Protocol to the Paris Agreement

Abstract: This paper describes the development of and gaps in knowledge in research on carbon accounting based on a systematic review of 117 papers published in influential accounting journals between 2005 and 2018. The review shows the literature has developed into four major streams of carbon accounting: carbon disclosure, management, performance and assurance, and that carbon accounting is emerging as a distinct discipline. Finally, our paper highlights future research opportunities to improve carbon accounting, so i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
108
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 146 publications
(190 reference statements)
2
108
0
6
Order By: Relevance
“…Climate change and its associated carbon emissions have piqued the interest of world leaders, researchers, organisations and the wider community. Carbon emissions have now become a contentious issue in a variety of disciplines over the last few years, for example, environmental studies [34], public health [35] and accounting [16,36,37]. Additionally, it is argued that government reforms regulations, and policies may compel organisations to disclose additional but voluntary environmental information [38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Climate change and its associated carbon emissions have piqued the interest of world leaders, researchers, organisations and the wider community. Carbon emissions have now become a contentious issue in a variety of disciplines over the last few years, for example, environmental studies [34], public health [35] and accounting [16,36,37]. Additionally, it is argued that government reforms regulations, and policies may compel organisations to disclose additional but voluntary environmental information [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the inception of the Kyoto Protocol and Paris Agreement, the carbon emissions literature has focused on four major streams: carbon emissions disclosure, management, performance and assurance, and established carbon accounting as a new or distinct discipline [37]. Prior research related to carbon disclosure heavily focused on capital market and corporate governance characteristics [17,37,45,46]. Existing studies found that the capital market does value carbon disclosure [46] and corporate boards' characteristics can affect voluntary carbon disclosure [17,45,47].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 In this era of energy shortages and environmental problems, the 'carbon neutrality' becomes a common objective of many countries (currently there are over 190 signatory countries agreed to a planned reduction of carbon emission in the Paris Agreement). 6 The threat of climate change also calls for a global revolution in buildings which closely connect architectural formation, environment performance, energy consumption and human behaviours (Figure 1). 7 As the issue of coexistence between architecture and environment gradually gained further recognition, architects have continued to redefine the connotation of architecture, the disciplinary value of environmental regulations as well as the resulting issues of architectural formation.…”
mentioning
confidence: 99%